1942
DOI: 10.1037/h0058086
|View full text |Cite
|
Sign up to set email alerts
|

Auditory sensitivity in the rat.

Abstract: The problem to which this paper is addressed issues from recent studies of the behavior called the neurotic pattern (6) or audiogenic seizure (9). Soon after this behavior was first reported (6), its crucial environmental determinant was shown to be an acoustic stimulus (8, 9), and as a consequence experimental work has been directed toward the quantitative definition of the role of acoustic variables in the production of the behavior. In particular, we undertook to determine the relative effectiveness of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1955
1955
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Five other published audiograms have been omitted. Of these, three are omitted because of inadequate calibration of stimulus intensities (Blackwell & Schlosberg, 1943;Gould & Morgan, 1942;Henry, 1938), a fourth is omitted because of the immeasurable effect of a progressive presbycusis during testing (Clack & Harris, 1963), and the fifth is omitted because noise bands instead of pure tones were used as stimuli (Harrison & Turnock, 1975). undoubtedly contribute to this variation.…”
Section: Discussionmentioning
confidence: 99%
“…Five other published audiograms have been omitted. Of these, three are omitted because of inadequate calibration of stimulus intensities (Blackwell & Schlosberg, 1943;Gould & Morgan, 1942;Henry, 1938), a fourth is omitted because of the immeasurable effect of a progressive presbycusis during testing (Clack & Harris, 1963), and the fifth is omitted because noise bands instead of pure tones were used as stimuli (Harrison & Turnock, 1975). undoubtedly contribute to this variation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the frequencies of maximum sensitivity have not been determined. Previous studies were either unable to measure the intensity of the signals used (Blackwell & Schlosberg, 1943;Gould & Morgan, 1942) or did not produce frequencies high enough to locate the region of maximum sensitivity (Clack & Harris, 1963;Cowles & Pennington, 1943;Gourevitch, 1965;Jamison, 1951). These studies suggested, however, that maximum auditory sensitivity was probably located above 10 kc.…”
Section: New York University Medical Schoolmentioning
confidence: 98%
“…There appear to be no discrimination studies with rats lo compare with the present results on this subject. What evidence is available (1,6,5,8,15) on absolute thresholds, however, suggests that the threshold for reinforcement (94 db.) found in the present study is much higher than absolute thresholds for sound with rats.…”
Section: -6mentioning
confidence: 99%